If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 8x + -33 Reorder the terms: -3 + 2x = 8x + -33 Reorder the terms: -3 + 2x = -33 + 8x Solving -3 + 2x = -33 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 2x + -8x = -33 + 8x + -8x Combine like terms: 2x + -8x = -6x -3 + -6x = -33 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + -6x = -33 + 0 -3 + -6x = -33 Add '3' to each side of the equation. -3 + 3 + -6x = -33 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = -33 + 3 -6x = -33 + 3 Combine like terms: -33 + 3 = -30 -6x = -30 Divide each side by '-6'. x = 5 Simplifying x = 5
| 6.2x+6.6-3.4x=20.6 | | 23=3x | | -17=3x-8 | | -5x+46=5+9(8x-4) | | a^3-1698a-2704=0 | | -4x-10=11 | | 1m+10=80 | | 33-x=222 | | 3(9x+7)=27x-1 | | 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 |